Integrating Qur’anic Ethics into Islamic Education Management: Conceptual Insights for Digital Learning Environments - Jurrofiq, Ahmad Rayhan; Nopiyanti, Eva; Putri, Hazara; Hakim, Lukmanul (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to conceptualize and formulate a Qur’anic value based model of Islamic Education Management that responds to the challenges of digital transformation. It seeks to examine how fundamental Qur’anic ethics, including honesty, justice, trustworthiness, civility, excellence, reliance on God, and verification, can be systematically integrated into educational governance to strengthen character formation while maintaining institutional effectiveness in digital learning environments. This research employs a qualitative descriptive design using library research. Data were collected from primary Islamic sources and secondary scholarly literature, including peer reviewed journal articles, academic books, and empirical studies on Islamic education management, digital pedagogy, and value based governance. The data were analyzed through qualitative content analysis and thematic synthesis to develop a conceptual framework that links Qur’anic ethical principles with the core management functions of planning, organizing, implementing, and evaluating. The findings indicate that Qur’anic values function not merely as moral ideals but as operational guidelines for educational management. Their integration enhances institutional accountability, ethical leadership, digital literacy, and holistic student development. Furthermore, technology optimization combined with value based governance creates learning environments that are both innovative and spiritually grounded. This study proposes an integrative conceptual model that systematically bridges Qur’anic ethics with modern management theory, offering a structured framework for Islamic education management in digital contexts, an area rarely addressed in previous research. The study provides theoretical enrichment for Islamic education management scholarship and offers practical guidance for policymakers, school leaders, and teachers in designing ethical, adaptive, and technology responsive educational institutions.